A Simplified Method for Fabrication of a Die Holder - Edgar N. Starcke, DDS (Journal of Prosthodontics, 2000)
RICHMOND S. HAYES patented the first articulator with descending condylar paths in 1889. In that same year, Hayes introduced the first example of a functional facebow-like device intended for locating the position of the casts correctly in the articulator.